An appraisal of geohydrological characteristics of Puri Sadar Block, Orissa, India - Rout, N.; Das, Madhumita (Journal of Nepal Geological Society, 2000)
The coastal wetlands are facing a great danger because of rapid and significant changes in the coastal system, especially in the near-shore areas. The present paper deals with the aquifer characteristics of the Puri Sadar Block (19 °45':19°55' N and 85°45': 86°00' E) by geophysical and geochemical methods. The average value of total dissolved so lid s (TDS) is 840 ppm and the cation and anion contents range from 0.1 to 10 mg/l, and from 7.8 to 5.400 mg/l, respectively. The maximum thickness of fresh aquifer is 30 m.